Leadership Development Through Design and Experimentation: Learning in a Research–Practice Partnership. (September 2018) - Rigby, Jessica G.; Forman, Stephanie; Fox, Alison; Kazemi, Elham
A core function of district leadership is providing instructional vision and support for school leaders and teachers. In this article, a Research–Practice Partnership focused on the improvement of elementary mathematics teaching and learning provides the context to study leadership development. We examine the process of one design team within the Research–Practice Partnership consisting of district leaders and university researchers using organizational learning. We found that as the team iteratively negotiated the design and implementation of a practical measure aimed at assessing and improving elementary mathematics instruction system-wide, the team's learning transformed the tools and routines of its work.